Development of transversal competences in dual training in the degree in BA - Beraza Garmendia, José María (Journal of Management and Business Education, 2023)
The main objective of this work is to know the perception of the Dual Itinerary graduates in the degree in Business Administration and Management on the development of transversal competencies, in order to contrast if these students really acquire the competencies established in the Degree Report to the same extent as the rest of the graduates in Business Administration and Management. To this end, a survey has been carried out with students participating in this Itinerary and other non-participating students, and it has been identified whether there are differences or not between both groups in the development of these competencies. The results show that, in general, students taking the Dual Itinerary value to a greater extent the importance of the transversal competencies of the degree for their professional future and consider that the degree in Business Administration and Management contributes to a greater extent to their development, in particular, analytical thinking and critical reflection, the application of acquired knowledge to work (and decision making), the making of reasoned judgments based on the data obtained and the development of learning skills to acquire a high degree of autonomy.